Social enterprises' impact on older people's health and wellbeing: exploring Scottish experiences. (9th October 2019) - Henderson, Fiona; Steiner, Artur; Mazzei, Micaela; Docherty, Catherine
Abstract: The global aging demographic is putting pressure on state-delivered health and social care services. As the austerity agenda in the UK cuts state-funded service provision for older people despite increasing demand, social enterprise has become a politically and economically attractive model for the sustainable delivery of some public services. Yet little is known about the impact of social enterprise on the health and wellbeing of older people. In this paper we address this gap in understanding and consider social enterprise activities as complex public health-promoting interventions. Our study aimed to understand what impact social enterprise activities had on the health and wellbeing of participants aged over 50, and also how that impact was created. To achieve this, we conducted qualitative semi-structured interviews with a sample ( n = 43) of staff, volunteers, clients and carers aged over 50 who were involved in activities delivered by three social enterprises. Using a thematic analysis to explore manifest and latent themes, two antecedents of subjective younger age emerged explaining how benefit was created, namely downward social comparison and identity . The social enterprise activities we studied benefited participants' health and wellbeing, impacting positively on participants' sense of purpose, social support, connectedness and inclusion. These health and wellbeing benefits can be considered as outcomes of complex public health interventions for older people, and we relate these outcomes to beneficial conditions within the intermediary social determinants of health. We conclude by discussing the future impact of social enterprise activities and current UK policy on the structural determinants of health.